A Case of Liquidity Risk: Demirbank (International Journal of Scientific Research and Management (IJSRM), 2022)
Liquidity risk is the possible loss of funds as a result of not being able to find the required amount of funds at an appropriate cost when needed or not being able to sell a financial asset at the required time and price. Briefly, it is the risk of maturity mismatch of cash inflows and outflows. Banks that use the short-term funds they collect in long-term assets are exposed to such a risk. Despite international regulations, it is observed that even in banks with sufficient capital levels, problems arise in the management and liquidity due to the change in risk appetites of different financial institutions in different periods. After the World War II, and especially with the effect of the liberalization policies of the Democratic Party in Türkiye, which was in ruling between 1950-1960, 24 new banks were established. In the case of Demirbank, which resulted to took over by the Savings Deposit Insurance Fund (SDIF) in 2000, especially all the process until the transfer of the bank to the fund, is a lesson to learn on liquidity risk management. In this article it is aimed to shed light on a period in Turkish banking history, the theoretical framework and the regulatory and supervisory processes and the reactions of related institutions.